Yoghurt biotherapy: contraindicated in immunosuppressed patients?. Issue 920 (1st June 2002) - MacGregor, G; Smith, A J; Thakker, B; Kinsella, J
Abstract : AUTHOR:e-mail address please A fatal case of Lactobacillus rhamnosus septicaemia after prolonged oral vancomycin for recalcitrant Clostridium difficile infection is reported. The patient was immunosuppressed with cyclophosphamide and steroids for Sjögren's syndrome. The administration of Lactobacillus spp as "biotherapy" may be hazardous in such circumstances.